PENGARUH LATIHAN POGO JUMP TERHADAP DAYA LEDAK OTOT TUNGKAI PADA TIM BOLA VOLI PUTRI SRIKANDI PEKANBARU - Lestari, Siti Nur; ', Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research that the leg muscle explosive power on the team is still lacking heroine Pekanbaru, this is seen in performing sports activities volleyball there are many flaws in the possession of the team included the lack or do not produce the jump is not so high jump while doing service, blocking and smash, this is because the authors suspect the team is less precise smash seen from the jump when the execution team did not jump high but jump quite low. This type of research is a kind of research experiments to see the effects of this form of exercise. The purpose of this study is to look at the effects of exercise pogo jump to the leg muscle explosive power of women's volleyball team pekanbaru heroine totaling 12 people. A sampling technique that by using total sampling, where the total population sampled. Data collection techniques derived from the pre-test and post test. Instrument in this study using the power vertical jump test as a tool for measuring the leap. Analyses were performed using t-test. based on data analysis and discussion, it can be concluded that there is significant influence of exercise pogo jump to the leg muscle explosive power in women's volleyball team proved to be the heroine pekanbaru thitung 14.119 and 1.796 Ttabel. Means thitung> Ttabel. At some level ɑ = 0.05.Key Words: Exercise Pogo Jump